Pengembangan Media Pembelajaran Menggunakan Animasi Pokok Bahasan Keunggulan Tanah Di Indonesia Mata Pelajaran IPS Terpadu Kelas VIII DI SMP N 2 Colomadu Kabupaten Karanganyar - KARUNIAWAN, KUKUH (2016)
This research was conducted at SMP N 2 Colomadu. The objective of this research was to know the criteria used for the development using the learning media of the 8th grade of production material in the form of animation video. In this research, the researcher used the development model developed by Walter Dick and Lou Carey. The development subject of this research was the students of Class VIII H of SMP Negeri 2 Colomadu. The data used for the product development of video media were quantitative and qualitative data. The techniques of data collection used in this research were Questionnair and Interview. The technique of data analysis used the technique of descriptive quantitative analysis in the forms of Validity Test, Reliability Test, Normality Test and Hypothesis Test using Paired Sample T Test. The results of this research showed that the development of the learning media in the form of video of Social Science subject on the material of land excellence in Indonesia used the development criteria that were: the presentation was in the forms of pictures and text, the explanation used was short, concise, and clear, accompanied by instrumental music, the video display was colorful, and the duration of video was long. The development of video was conducted as well as possible by meeting the criteria suitability needed in the making of learning media in the form of video that could reach the objectives of learning. The development of video media used when the learning occured in the experimental class was effective and could be seen from the result of average of experimental class that the pre test score was 67.7 and the post test score which obtained the treatment of learning media in the form of video was 92.3 that experienced an increase as much as 10.5, meanwhile, in the control class, the pre test score was 60.8 and the method used was the lecturing method, which had post test score of 71.5 and experienced an increase as much as 10. Therefore, the results of the two classes showed that the use of learning media in the form of video was more efective than the use of lecturing method.